TERRITÓRIO DA CIDADANIA NOROESTE COLONIAL: O USO DAS TECNOLOGIAS DA INFORMAÇÃO E COMUNICAÇÃO - Deckert, Cristiele T.; Benso, Aline; Allebrandt, Sérgio L.; Oliveira, Vinicios G. d. (Salão do Conhecimento, 2013)
Resumo